2019
DOI: 10.1186/s13293-019-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor profiles across tissues from male and female Rattus norvegicus

Abstract: BackgroundEstrogen is formed by the enzyme aromatase (CYP19A1) and signals via three identified receptors ERα (ESR1), ERß (ESR2), and the G protein-coupled estrogen receptor (GPER). Understanding the relative contribution of each receptor to estrogenic signaling may elucidate the disparate effects of this sex hormone across tissues, and recent developments in PCR technology allow absolute quantification and direct comparison of multiple targets. We hypothesized that this approach would reveal tissue- and sex-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
73
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 49 publications
10
73
1
1
Order By: Relevance
“…regulates the renal medullary P2 system. Notably, renal estrogen receptor, ER, expression has been shown in multiple studies [36][37][38]. Binding studies using radiolabeled E2 revealed that radioactivity localizes to the proximal tubule and the inner medullary collecting duct [39], which is relevant to our findings in mIMCD3 cells.…”
Section: Discussionsupporting
confidence: 68%
“…regulates the renal medullary P2 system. Notably, renal estrogen receptor, ER, expression has been shown in multiple studies [36][37][38]. Binding studies using radiolabeled E2 revealed that radioactivity localizes to the proximal tubule and the inner medullary collecting duct [39], which is relevant to our findings in mIMCD3 cells.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, considering that a single post‐training administration of G1 was able to restore memory in both iron‐ and iron‐OVX rats, we can propose that the stimulation of GPER contributes to memory consolidation by ameliorating memory deficits. In addition, a very recent study reported that GPER is highly expressed in brain areas such as the somatosensory and prefrontal cortex in both sexes, with its expression in these areas being higher than classical oestrogen receptors ERα and ERβ . Because G1 was administered systemically, its positive effects on cognition may be related to GEPR stimulation in other brain areas implicated in memory consolidation such as the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a very recent study reported that GPER is highly expressed in brain areas such as the somatosensory and prefrontal cortex in both sexes, with its expression in these areas being higher than classical oestrogen receptors ERα and ERβ. 45 Because G1 was administered systemically, its positive effects on cognition may be related to GEPR stimulation in other brain areas implicated in memory consolidation such as the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…ERα and GPER are expressed at similar levels in cardiac tissue from male and female rodents (46) as well as from humans (47). In contrast, reports of ERβ expression in the heart are conflicting, with ERβ mRNA detected in human cardiac tissue (48) but remaining below detectable levels in rodent cardiac tissue (46,49). Based on observed improvement in cardiac function in response to E 2 treatment in postmenopausal women (50) and in ovariectomized (OVX) rats (21), researchers have attempted to identify the primary receptor mediating estrogen's cardioprotective effects.…”
Section: Estrogen Receptors In the Heartmentioning
confidence: 99%
“…G15 and G36 are antagonists of GPER with low affinity binding to the classical estrogen receptors (64). While the exact signaling actions and transduction pathways of cardiac GPER are not completely understood, they are likely dependent on the cell type, site of action and the relative levels in comparison with the other estrogen receptors (46). The selective GPER agonist G1 modulates fast transduction pathways in the heart that are involved in (1) controlling intracellular calcium via actions on cardiac channels and pumps, (2) regulating phosphoinositide 3kinase (PI3Ks) and extracellular signal-related kinases (ERKs), and (3) modulating cyclic adenosine monophosphate (cAMP) (see sections Effects of Estrogen and GPER Activation on I Ca,L and Estrogen, GPER, and SERCA2a and Its Regulatory Proteins below).…”
Section: Estrogen Receptors In the Heartmentioning
confidence: 99%